PRINCIPLES OF POLICY THOUGHT a philosophical approach to public policy. - Yi, Hae-yŏng, 1958- ([S.l.] : ROUTLEDGE, 2023)
Policy thought integrates the why of political philosophy and the how of public policy formulation. Lee outlines five key principles for the development of policy thought: The Principle of Policy Statism The Principle of Policy Goodness The Principle of Policy Balance The Principle of Policy Practicality The Principle of Policy Humans: Interpenetrated Policy Humans with Non-humans Each principle is derived from a combination of Confucian and other East Asian philosophies, as well as contemporary Western political philosophy. In combination they offer an innovative approach to formulating, configuring and assessing public policy, with ethics and efficacy. An essential guide to incorporating big picture philosophical questions into pragmatic policy for students, practitioners and scholars of public policy and administration.
OCLC-licensed vendor bibliographic record.
Keywords: Political planning; POLITICAL SCIENCE / Public Policy / General; PHILOSOPHY / Ethics & Moral Philosophy